An Expanding Neighbourhood Search Technique for Avalanche Search-and-Rescue Operations using Air Ground Collaborative Wireless Networks - Azad, Saiful; Rahman, Md. Arafatur; Kabir, M. Nomani (Science Publishing Corporation, 2018)
Due to avalanches, a considerable number of travellers deceases every year. The number is increasing over the past few decades. Hence, to speed up the rescue mission and thereby, to mitigate number of fatalities, collaborative rescue missions are envisioned. However, most of the existing techniques that are utilized in rescue missions are non-collaborative. In this paper, we propose a new searching technique, named Expanding Neighbourhood Search Technique (ENST) to facilitate collaborative rescue missions. We performed an extensive simulation campaign and compared our proposed technique with other prominent existing techniques to find out the effectiveness of the proposed scheme.